Compliance of "risk" insurers with solvency and investment activity requirements in Ukraine - Лобова, Оксана Миколаївна; Моташко, Тетяна Петрівна; Прокоф'єва, Олена Володимирівна (Київський національний університет імені Тараса Шевченка, 2025)
B a c k g r o u n d . Ensuring the financial stability of insurance companies is particularly important in an unstable economic environment, in particular given the macroeconomic challenges are caused by inflation, war and the devaluation of the national currency. In addition, this aspect is particularly important for protecting the interests of policyholders. The purpose of the article is to analyze the compliance of risk insurers with the new requirements for solvency and investment activities introduced in 2024. M e t h o d s . The methods of financial analysis, content analysis and statistical data processing were used. The content analysis helped to identify requirements for insurers in terms of solvency and investment activity. Financial analysis was used to assess the financial performance of companies. Statistical data processing was used to calculate the currency risk ratio, financial stability ratio and other indicators. The obtained indicators were compared with the regulatory requirements and the own assessment of compliance was made. R e s u l t s . The author proposes to divide ‘risky' insurers into 3 groups according to the level of risk. The classification is an author's proposition, which is based on generally accepted financial indicators. They were adapted to the conditions of the Ukrainian insurance market. The research sample consisted of three insurance companies that represented different levels of risk in the Ukrainian market. An examination of their solvency and investment activities for compliance with the new NBU requirements revealed that the companies demonstrate different levels of compliance with these requirements. Non-compliance with the requirements highlights the importance of sufficient regulatory capital to maintain the resilience of insurance companies in the face of economic uncertainty. The analysis of investment activities showed that companies invest only in a limited set of long-term and short-term financial instruments, which are determined based on the basis of financial statements and the lack of wider asset diversification. C o n c l u s i o n s . It is established that, despite the legislative changes, the risks for them remain significant. The research has shown that companies with a lower financial strength ratio have limited opportunities to diversify their investment portfolios. This creates additional pressure on their solvency. Companies need to develop new mechanisms to stabilize capital and improve risk management efficiency, taking into account currency volatility, NBU requirements and international standards.

В с т у п . Забезпечення фінансової стійкості страхових компаній особливо актуально в умовах нестабільної економічної ситуації, зокрема з огляду на макроекономічні виклики, пов'язані з інфляцією, війною та девальвацією національної валюти. Цей аспект особливо важливий задля захисту інтересів страхувальників. Метою статті є дослідження відповідності ризикових страховиків новим вимогам щодо платоспроможності та інвестиційної діяльності, запроваджених із 2024 року. М е т о д и . Застосовано методи фінансового аналізу, контент-аналізу та статистичної обробки даних. Контент аналіз дозволив виявити вимоги до страховиків щодо платоспроможності та інвестиційної діяльності. Фінансовий аналіз застосовано для оцінювання показників фінансової діяльності компаній. Статистичну обробку даних використано для обчислення показників відношення валютних ризиків, коефіцієнта фінансової стійкості тощо. Застосовано зіставлення отриманих показників з нормативними вимогами та надання власної оцінки відповідності. Р е з у л ь т а т и . Запропоновано розділити "ризикових" страховиків на 3 групи за рівнем ризику. Класифікація є авторською пропозицією, заснованою на загальноприйнятих фінансових показниках, адаптованих до умов українського ринку страхування. Вибірка дослідження складалася з трьох страхових компаній, які представляли різні рівні ризику на українському ринку: СГ "Оберіг", СК "Ультра Альянс" і ТДВ СК "Альфа-Гарант". У процесі дослідження їхньої платоспроможності та інвестиційної діяльності на відповідність новим вимогам НБУ встановлено, що компанії демонструють різний рівень дотримання цих вимог, що характеризує неоднорідність ринку. Недотримання вимог вказує на важливість достатнього регулятивного капіталу для підтримання стійкості страхових компаній в умовах економічної невизначеності. Аналіз інвестиційної діяльності показав, що компанії інвестують лише в обмежений набір довгострокових і короткострокових фінансових інструментів, які визначені на базі даних фінансової звітності та відсутності ширшої диверсифікації активів. В и с н о в к и . Встановлено, що, незважаючи на проведені законодавчі зміни, ризики для страховиків залишаються значними. З'ясовано, що компанії з нижчим коефіцієнтом фінансової стійкості мають обмежені можливості для диверсифікації інвестиційних портфелів. Це створює додатковий тиск на їхню платоспроможність. Компаніям необхідно розробляти нові механізми стабілізації капіталу та підвищення ефективності управління ризиками, враховуючи волатильність курсу валюти, вимоги НБУ та міжнародні стандарти.
Дотримання вимог "ризиковими" страховиками до забезпечення платоспроможності та інвестиційної діяльності в Україні
Keywords: Solvency of insurers; investment activity; regulatory capital; currency risks; insurance companies; financial stability; Solvency II; Solvency of insurers; investment activity; regulatory capital; currency risks; insurance companies; financial stability; Solvency II.; платоспроможність страховиків; інвестиційна діяльність; регулятивний капітал; валютні ризики; страхові компанії; фінансова стійкість; Solvency II; Платоспроможність страховиків; інвестиційна діяльність; регулятивний капітал; валютні ризики; страхові компанії; фінансова стійкість; Solvency II.